Catch-22 - Heller, Joseph (Simon & Schuster Paperbacks, 2011)
This fiftieth-anniversary edition commemorates Joseph Heller’s masterpiece with a new introduction by Christopher Buckley; personal essays on the genesis of the novel by the author; a wealth of critical responses and reviews by Norman Mailer, Alfred Kazin, Anthony Burgess, and others; rare papers and photos from Joseph Heller’s personal archive; and a selection of advertisements from the original publishing campaign that helped turn Catch-22 into a cultural phenomenon. Here, at last, is the definitive edition of a classic of world literature.